Optimizing root yield of cassava under fertigation and the masked effect of atmospheric temperature - Omondi, J.O.; Yermiyahu, U.; Rachmilevitch, S.; Boahen, S.; Ntawuruhunga, P.; Sokolowski, E.; Lazarovitch, N. (Wiley, 2020)
BACKGROUND Fertigation is a rare and an expensive method of fertilizer application to cassava, and hence there is a need to optimize its efficiency for profitability. This study's objective was to optimize root yield of cassava through fertigation using a logistic model.